(untitled) (Revista de Estudos da Linguagem, 1996)
This paper aims at analyzing certain cases of elision of Ib,d,g/ in intervocalic position taking into consideration both syllabic stnlt.’ture anel the number of syllables. 111e elialect t.meler stuely is the Argentine Spanish of Rosario, dty which belongs to the linguistic region of the Río ele la Plata. Finally, the results obtaineel in our analysis are contrasted to John Harris’ point ofview (989) in order to ielentify in which stage within Lexical Phonology these phenomena are placed.